Maternal and fetal outcomes of pregnant women on antiretroviral (ARV) therapy at Dr George Mukhari hospital :a case-controlled clinical study - Mavukani, M. P. (University of Limpopo (Medunsa Campus), 2009)
OBJECTIVE: The objectives of the study were: 1) To determine the pattern of toxicity/side-effects among women using Highly Active Antiretroviral Therapy (HAART) in the perinatal period in comparison with women who were treated with intra- partum prophylaxis of nevirapine at the time of delivery. 2) To evaluate the effects of either approach of therapy on maternal and fetal outcomes. METHODOLOGY: STUDY DESIGN The department of Obstetrics and Gynaecology has begun to administer HAART to pregnant women identified for ARV programme. These women were counseled and recruited prospectively for the study. The study involved comparison of pregnancy outcomes between women identified for HAART and those who were HIV infected but who only required intra-partum prophylaxis in labour to prevent mother-to-child transmission of HIV with nevirapine.
Thesis (M Med.(Obstetrics & Gynecology))--University of Limpopo,2009.
Keywords: Antiretroviral therapy; Pregnant women